Optimum time to refurbish a boiler feed pump at Eskom's power stations - Mortlock, Steven Peter (Department of Mechanical Engineering, 2014)
A key focus area in power generation today is to improve equipment and plant efficiency, with this study specifically aimed to determine the optimum time to refurbish a boiler feed pump by analysing the internal wear of the annular seals. The boiler feed pump (BFP) installed in a power station is either driven by a steam turbine or an electric motor and the BFP is the highest auxiliary power consumer within the power station. In the 13 Eskom generating fossil fired power stations the installed BFPs consume approximately 1000 MWs of auxiliary power continuously. The focus of the study is to understand how the BFPs efficiency changes with time as a result of increased internal clearances and the effect this has on the auxiliary power consumption. An in-depth analysis of the efficiency degradation has been studied to understand the contributing factors to these changes and specifically the change in leakage rate and friction in the annular seals of the impellers and axial thrust balancing devices.